Health of elderly tribes: a community based clinico-epidemiological study in West Bengal, India - Basu, Gandhari; Mondal, Poulomi; Roy, Suman K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Reported literatures suggested that health of elderly, mainly tribes, still remains unsatisfactory. They are the most neglected and highly vulnerable to diseases with high degree of morbidity and mortality. The present study was conducted to measure the overall health status and awareness of any beneficial scheme and also associated factors among the elderly tribes. Methods: A community based, cross sectional survey was conducted among 120 elderly tribes, for three months. Data on socio-demographic attributes, self-reported morbidities and mental health parameters was collected by direct interview with a predesigned, structured proforma. Clinical examination was done to find out any systematic morbidity. Anthropometric measurements, blood pressure were recorded by standardized instruments. Prevalence of stress was assessed by general health questionnaire (GHQ-12). Data was analysed by licensed SPSS 20.0. Results: Out of 120 elderly tribes, majorities were female (61.7%), aged between 60 to 69 years. The mean (SE) age was 64.50 (0.421) years. Ninety nine subjects were illiterate. Tobacco addiction was noted in 84.3% elderly. Common cold (80.0), low back pain and joint pain (73.3%), alcohol addiction (63.3), smoking (56.0), problems of vision (50.0) were also common. Overweight, hypertension and pallor was noted in nearly half. Women were more affected. One in every four felt unhappy or depressed. Severe distress was found among one in every five respondents. Distress was more in persons aged more than 70 years, illiterate and in lower social class (p<0.05). Conclusions: There is a high prevalence of social problems like illiteracy, unemployment, financial dependence, morbidities and stress among the elderly tribes.